Branchless banking agents: Business satisfaction, continuity, and viability - Hilman Palaon; Sudarso Kaderi Wiryono; Taufik Faturohman (Cogent Business & Management, 2020)
Branchless banking agent business is growing in many developing countries. Agents are an extension of financial services providers to serve the last mile customers. We adopted the framework of satisfaction theory to analyze the satisfaction and business continuity of branchless banking agents. Our research data were collected using computer-assisted personal interviews (CAPI) from 768 branchless banking agents in Indonesia. Small business success factors are used to determine our hypotheses. Structural equation modelling (SEM) and descriptive statistics were used for data analysis. In-depth analysis was performed to assess business viability using business model canvas (BMC). Apart from financial factors, non-financial factors were also found to have influences on business owners' satisfaction. Social contribution is one of the reasons for them to become bank agents, which is to channel social assistance programmes. We recommend financial services providers to improve agents' skills in serving customers and to provide monthly target transactions. Finally, the reliability of supporting infrastructure, especially the Internet network and the system or applications used by agents, is required for the sustainability of this business.
Keywords: 650; branchless banking; mobile money; business model; satisfaction; continuity; viability; Indonesia